Estudo das propriedades dielétricas na faixa das micro-ondas durante a reação de transesterificação para produção de biodiesel - Taques Filho, Eduardo Gaspar Ribeiro (2015)
In order to optimize the use of microwave in chemical reactions it is necessary the knowledge of the dielectric properties of the reaction mixture and/or of one of their specific constituents, since the knowledge of how each material absorbs or dissipates the incoming microwave radiation allows achieving better results in microwave-assisted chemical reactions. The main goal of the present work is to develop of new methodologies to study the dielectric properties of reactions mixtures and thus providing a better use of microwaves in chemistry with a focus in organic reactions and processes associated with biofuels production. In this work it is investigated the dielectric properties of reaction mixtures during transesterification reaction to biodiesel production, by varying the kind of alcohol, oil and acids employed. Measurements were carried out in homogeneous acid-catalyzed reactions employing ethylic and methylic alcohols and purified and waste Brazil nut oil as well as soybean and babassu oils. As catalysts, it was employed sulfuric acid, methane sulfonic, chloro sulfuric and phosphoric acids. The measurements were performed in the range of 0.3 to 13GHz, and reaction temperatures for methylic and ethylic reactions were 60 °C and 70 °C respectively. The stirring speed of the reaction mixtures were evaluated, and the ideal speed is that allows a better conversion without interfering in the dielectric measurements. Phosphoric acid demonstrated poor catalytic activity in transesterification reactions to biodiesel production since after 12 hours of reaction the conversion did not achieved 10%. On the other hand, chlorosulfuric and methane sulfonic acids showed better catalytic activity than sulfuric acid in the same reaction time, achieving conversions to biodiesel greater than 70%. From the different kind of the oils employed it was observed that the chemical nature of the oil affects the conversion to biodiesel.